Effect of bio-priming on germination and growth of Sugar Beet cultivars (Beta vulgaris L.) - F. Bahramian; A. Abbasi Surki; A. Jamali Zavare; F. Sharifzadeh (علوم و فناوری بذر ایران)
Bio-priming and application of bio-fertilizer has special importance in crop production and sustainable soil fertility. Growth and quality improvement with environment-friendly microorganism have been proved in crops. In order to evaluation of bio-priming possibility in seed improvement of sugar beet cultivars, effects of two bacteria species including Pseudomonas fluorescens and Pseudomonas putida on seed germination and growth indices were evaluated. Experiment was directed as factorial in randomized complete block design with four replication, there in experimental factors were bacteria species including Pseudomonas fluorescens, Pseudomonas putida and no bacteria as control for first factor, and beet cultivars including Pars, Torbat and line 31782 as second factor. Germination percentage affected with cultivar, bio-priming and their interaction, but germination rate was only affected by bio-priming. The highest germination percentage and was related to Pseudomonas putida and Pars cultivar. Application of bacteria increased germination rate versus control. Other mean comparison showed that Pseudomonas fluorescens increased root length, shoot length and seedling length and Pars and Torbat cultivars has more root and shoot length rather than Line 31782. Bio-prime with Pseudomonas fluorescens and Pseudomonas putida enhanced Vigor Index I, but Vigor Index II was only affected by cultivar. Pars and Torbat cultivar had higher germination traits and Vigor Index I and II to Line 31782 and showed more reactions to treatments. Generally, Bio-primingtreatments affected sugar beet cultivars versus control. Both bacterial strain act identically but Pseudomonas putida had more effects on cv. Pars.